Slow Digital Art History in Action: Project Cornelia's Computational Approach to Seventeenth-century Flemish Creative Communities. (3rd April 2019) - Brosens, Koenraad; Aerts, Jan; Alen, Klara; Beerens, Rudy Jos; Cardoso, Bruno; De Prekel, Inez; Ivanova, Anna; Lamqaddam, Houda; Molenberghs, Geert; Slegten, Astrid; Truyen, Fred; Van der Stighelen, Katlijne; et al.
Abstract : This paper presents the rationale, genesis, and applications of Project Cornelia, an ongoing computational art history project developed by a cross-disciplinary team at the KU Leuven (University of Leuven). It shares practical perspectives acquired while conceptualizing and unfolding the project and discusses successes as well as challenges and setbacks. In doing so, this paper is a cautionary tale for art historians entering the digital arena. However, it is also an invitation to connect to Project Cornelia. Art historians seeking to avoid heavy start-up costs and willing to embed their research in a larger empirical and theoretical framework can easily share their data and use Cornelia 's data and tools to further their and our understanding of the genesis and governance of early modern creative communities and industries.